Teaching and facilitation implementation methods among lecturers and their influence on students' interests in learning geography - Mohd Isa, Nor Kalsum; Ab Samat, Muhammad Yusoff; Govindasamy, Priyalatha; Mohd Isa, Nor Junainah; Nursa’ban, Muhammad; Mohd Yunos, Mohd Yazid; Ibrahim, Mohd Hairy; Ismail, Kamarul (ournal of Language and Linguistic Studies, 2021)
This study aimed to examine the implementation of the teaching and facilitation (PdPc) methods among lecturers and their influence on students' interests in learning Geography. Students' interests in learning were measured based on two aspects: emotionaland cognitive aspects. A survey approach was used in this study, involving a total of 120 final year students (seventh semester) who have completed all the eight Geography core subjects offered in Universiti Pendidikan Sultan Idris (UPSI). The sample was selected using a simple random sampling method. A set of questionnaires with 40 items was distributed to the respondents. The findings from the descriptive analysis indicated that the overall students' interests in learning Geography subjects in UPSI was at a high level (M=4.19, SD=0.83). Additionally, the analysis also discovered that the implementation of the PdPc methods in the Geography subjects using the traditional learning method was moderate (M=2.72, SD=1.34), while the game-based learning method was at a high level (M=4.27, SD=0.75), the flipped-based learning method was at a high level (M=4.32, SD=0.78), and the challenge-based learning method was also at a high level (M=4.36, SD=0.71). The Pearson correlation analysis revealed that students’ emotional interests and cognitive interests had a relationship with all the learning methods. The multiple linear regression analysis indicated that the game-based learning method was the method that had the most influence on students' interests in learning the geography subjects with a percentage contribution value of 64.5 percent. Therefore, PdPc methods that are creative and go beyond traditional learning need to be implemented by lecturers to attract interest in learning Geography and further achieve student development.